Adsorption effect of a cationic surfactant at carbon paste electrode as a sensitive sensor for study and detection of folic acid. (January 2016) - Behpour, Mohsen; Attaran, Abdol Mohammad; Sadiany, Mahdi Mollaei; Khoobi, Asma
Highlights: A novel studies on adsorption of a cationic surfactant at carbon paste electrode. Preparation of a sensor for folic acid (FA) based on enhancement effect of CTAB. Electrochemical studies of FA in the presence of CTAB by various techniques. Increasing sensitivity in detection of FA in the presence of CTAB. Capability of the proposed method for FA recovery in real samples. Abstract: The present study is the first report on the effect of cetyltrimethylammonium bromide (CTAB) on the electrochemical behavior of folic acid (FA) at the surface of carbon paste electrode (CPE) in real samples. The studies were performed by cyclic voltammetry (CV), chronocoulometry and differential pulse voltammetry (DPV). CTAB, with a hydrophobic C–H chain, could absorb at the CPE surface by hydrophobic interaction and then changed the electrode/solution interface, and eventually affects the electrochemical response of FA, confirming from the remarkable oxidation peak current enhancement. For investigation of the electrode properties, CV technique was used at the various scan rates. Electrochemical parameters including diffusion coefficient ( D ), electron transfer coefficient ( α ) and ionic exchanging current density ( j o ) were determined for the FA at the surface of the electrode. Under optimized conditions, the proposed method showed acceptable analytical performances for FA in terms of linearity (over the concentration range from 0.01 to 1.5 and 1.5 to 10.0 μM), detection limit (2.89 nM), repeatability (1.37%) and stability (13% reduction in peak current after 60 days). After studying on the effect of probable interferences it was found that the method was free of the interferences. Finally, the proposed method was successfully applied for the determination of FA in real samples.